2004
DOI: 10.2134/jeq2004.3300
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Analysis of Whole Soils and Sediment

Abstract: Thermal analysis techniques were utilized to investigate the thermal properties of two soils and a lignite coal obtained from the International Humic Substances Society (IHSS), and sediment obtained from The Netherlands. Differential scanning calorimetry (DSC) revealed glass transition behavior of each sample at temperatures ranging from 52 degrees C for Pahokee peat (euic, hyperthermic Lithic Medisaprists), 55 degrees C for a Netherlands (B8) sediment, 64 degrees C for Elliott loam (fine, illitic, mesic Aquic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 48 publications
3
29
0
Order By: Relevance
“…TMA has been applied to study glass transition behaviour in NOM fractions and organic whole soils and sediments (Young and LeBoeuf 2000;DeLapp and LeBoeuf 2004;. The potential of TMA for granular and heterogeneous soil material is, however, imparted by sample consistency.…”
Section: Introductionmentioning
confidence: 99%
“…TMA has been applied to study glass transition behaviour in NOM fractions and organic whole soils and sediments (Young and LeBoeuf 2000;DeLapp and LeBoeuf 2004;. The potential of TMA for granular and heterogeneous soil material is, however, imparted by sample consistency.…”
Section: Introductionmentioning
confidence: 99%
“…They found that repellency increased during heating up to 200°C, but was eliminated at temperatures >200°C due to the destruction of SOM. Several studies have also used thermal analysis to identify specific domains within soils that are responsible for nonlinear and linear sorption behaviors important to contaminant transport in the environment (DeLapp and LeBoeuf, 2004). Conceptual models suggest that nonlinear sorption behavior is attributable to rigid, glass-like regions in SOM, while linear sorption is attributable to more fluid, gel-like regions.…”
Section: Thermal Analyses For Other Som Propertiesmentioning
confidence: 99%
“…Pore volume changes of up to 10% can occur in the shallow horizons of undisturbed peatlands and up to 15% in recently harvested peatlands (Price, 2003). Peat shows only a 0Ð5% expansion of volume during a 10-30°C increase of temperature (DeLapp and LeBoeuf, 2004), suggesting the effect of thermal expansion on VWC is minimal. These processes alter porosity and must be considered before VWC can be used as an indicator of soil water availability.…”
Section: Volumetric Water Contentmentioning
confidence: 99%